Gene silencing of Ganoderma boninense Lanosterol 14α-demethylase (GBERG11) affects ergosterol biosynthesis and pathogenicity towards oil palm - Lim, Fook Hwa; Rasid, Omar Abd; Idris, Abu Seman; As'wad, Abdul Wahab Mohd; Vadamalai, Ganesan; Parveez, Ghulam Kadir Ahmad; Wong, Mui Yun (Elsevier B.V., 2024)
Oil palm plays an essential role in securing the global vegetable oil supply, is prone to the stem rot disease caused by several basidiomycete Ganoderma species, especially Ganoderma boninense. Various mitigation efforts were initiated aiming to tackle the disease, including the study of the fungal pathogen at omics level. However, the functional genomic study protocol is unavailable for G. boninense, which is required for validating the potential pathogenicity genes identified from this fungal species. This is the first report on the development of a molecular tool for gene manipulation study of G. boninense Lanosterol 14α-demethylase (GbERG11) via RNAi-mediated gene silencing. Three Dicer and six Argonaute homologs were identified based on BLASTn analysis on G. boninense genome database. Three hpRNA vectors corresponding to different regions of GbERG11 were prepared and transformed into G. boninense to generate the RNAi-ERG11 transformants. The RNAi-ERG11 transformants were evaluated based on the growth rate, GbERG11 gene expression, biosynthesis of ergosterol and pathogenesis towards oil palm. The RNAi-ERG11 transformants have shown reduced growth, expression of GbERG11 and ergosterol production compared with the wild type. Three representative transformants with the least GbERG11 gene expression were subjected to oil palm in vitro inoculation study. Results showed that the oil palm plantlets inoculated with RNAi-ERG11 transformant (TGL20–2–4) demonstrated significant reduced infection symptoms at the initial stage of the study. On average, the RNAi-ERG11 transformants (TGL20–2–4 and TGL20–3–1) inoculated with oil palm showed a significant reduction of ERG11 gene expression and produced a lower amount of ergosterol as compared to the wild type. The knowledge generated from this study imparts the understanding on the correlation between GbERG11 gene expression and the biosynthesis of ergosterol and fungal pathogenicity. Furthermore, the gene manipulation tool developed in this study can be applied for functional study of other G. boninense genes especially those that are involved in the fungal pathogenicity. Gene silencing of GbERG11 could be extended to inhibit Ganoderma infection in oil palm via host/spray-induced gene silencing.